The impact of empirical hydrocortisone therapy on clinical outcomes in dengue fever: a retrospective chart review. (20th June 2020) - de Mel, Sanjay; Thilakawardana, Basuru Uvindu; de Mel, Primesh; de Silva, Arjuna P; de Mel, Chandima; Chandrasena, Lal; Seneviratne, Suranjith L; Abeysuriya, Visula
Abstract: Background: The role of steroids in dengue infection (DI) remains uncertain. Methods: A retrospective chart review was conducted on patients ≥18 y of age diagnosed with DI based on positivity for dengue non-structural antigen 1 or immunoglobulin M between October 2017 and November 2018. Results: Hydrocortisone was administered to 106 of 406 patients. DI with warning signs occurred in nine patients (9.5%) in the steroid cohort and eight patients (2.5%) in the non-steroid group. The incidence of severe DI, bleeding and admission duration were similar between the groups. Conclusions: Our study shows no significant benefit of empirical steroids in DI.